Analysis of Handler Hygiene with Coliform Content at Drinking Water Depots in the Former Maospati District, Magetan Regency in 2024 - Sari, Alvyani Novita; Ratnawati, Riska; Nur R, Karina (Syntax Corporation Indonesia, 2024)
This study aims to analyze the relationship between handler hygiene and the content of coliform bacteria in drinking water depots in the former Maospati District, Magetan Regency in 2024. Coliform bacteria are used as an indicator of fecal contamination in drinking water, which can pose serious health risks for consumers. The research method used is analytical observational with a cross-sectional approach. Sampling was carried out at simple random from 52 drinking water depots, with a total of 19 samples analyzed using the Most Probable Number (MPN) method to determine the concentration of coliform bacteria. The research results showed that the majority of drinking water depots (59%) had poor handler hygiene, while the remaining 41% had good hygiene. Microbiologically, 51.3% of water samples did not meet the requirements because they contained coliform bacteria, while 48.7% met the requirements. Statistical analysis showed a significant relationship between poor handler hygiene and high levels of coliform content (p = 0.001), with a relative risk 12.2 times higher. This study makes an important contribution to knowledge about drinking water safety in the region, highlighting the importance of sanitation and hygiene monitoring in drinking water depots to reduce public health risks. Recommendations from this research include increased supervision and training for drinking water depot managers, as well as the need to strengthen regulations and implement stricter sanitation hygiene standards.